GABA uptake via the GABA permease GabP represses virulence gene expression in Pseudomonas syringae pv. tomato DC3000 - McCraw, S; Park, D; Bentley, M; Rico, A; Ratcliffe, R; Kruger, N; Collmer, A; Preston, G (American Phytopathological Society, 2016)
The non-protein amino acid γ-aminobutyric acid (GABA) is the most abundant amino acid in the tomato (Solanum lycopersicum) leaf apoplast and is synthesised by Arabidopsis thaliana in response to infection by the bacterial pathogen Pseudomonas syringae pv. tomato DC3000 (Pst DC3000). High levels of exogenous GABA have previously been shown to repress the expression of the type III secretion system (T3SS) in Pst DC3000, resulting in reduced elicitation of the hypersensitive response (HR) in the non-host plant tobacco (Nicotiana tabacum). This study demonstrates that GABA permease (GabP) provides the primary mechanism for GABA uptake by Pst DC3000, and that the gabP deletion mutant ΔgabP is insensitive to GABA-mediated repression of T3SS expression. ΔgabP displayed an enhanced ability to elicit the HR in young tobacco leaves and in tobacco plants engineered to produce increased levels of GABA, which supports the hypothesis that GABA uptake via GabP acts to regulate T3SS expression in planta. The observation that P. syringae can be rendered insensitive to GABA through loss of gabP, but that gabP is retained by this bacterium, suggests that GabP is important for Pst DC3000 in a natural setting, either for nutrition, or as a mechanism for regulating gene expression.